2023
DOI: 10.3390/prosthesis5030059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of the Use of Low-Cost TKA Prosthesis in Low Budget Countries—A Narrative Review

Edoardo Bori,
Clara Deslypere,
Laura Estaire Muñoz
et al.

Abstract: Despite the orthopedics markets in the US and the EU reaching a plateau, the market size in countries such as Brazil, Russia, India, and China is steadily growing. As a result, major orthopedic companies are shifting their focus towards these markets and developing products tailored to their needs. However, a significant challenge associated with this new opportunity is the requirement for the development of more affordable prostheses compared to those sold in the US and Europe. With the introduction of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…NSAIDs can cause ulcers and bleeding in the gastric tract. Studies in the USA found that about 16,000 people die from gastrointestinal side effects [39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs can cause ulcers and bleeding in the gastric tract. Studies in the USA found that about 16,000 people die from gastrointestinal side effects [39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should aim to fill this gap by conducting well-designed prospective studies with larger sample sizes and longer follow-up periods. Additionally, it is crucial to explore the potential influence of different types and regimens of ERT on TMDs to provide a better understanding of this association [ 30 37 ]. The impact of this review on the literature is significant, as it consolidates the existing evidence and provides a comprehensive analysis of the relationship between ERT and TMDs.…”
Section: Discussionmentioning
confidence: 99%
“…Power ridges are small, elevated areas on the aligners that help to move specific teeth. Anchorage devices are used to stabilize teeth or groups of teeth during the orthodontic treatment process ( Bori et al, 2023 , Russell and Bergmann, 2023 , Yokoyama et al, 2023 , Garino et al, 2016 , Minervini et al, 2017 ). The aligner auxiliaries improves the accuracy and efficiency of clear aligner treatment as they provide additional force to move teeth, helping to correct bite problems, and enable orthodontists to treat a wider range of orthodontic issues.…”
Section: Introductionmentioning
confidence: 99%